Sunday Star, 19 April 2009 - Chapman, Karen; Lee, Yuk Peng (The Star (Malaysia), 2009)
Thirty per cent of the primary School Assessment Test (UPSR) will account for a child's results when a new curriculum is introduced for Year One pupils from next year.